Odpowiedzi

Najlepsza Odpowiedź!
2009-09-13T11:22:42+02:00
(+12)-(-16)-(+6)+(+20) = 10

-20-(-5)+(-17)-(-3)=- 29

-(-11+14)-(16-13)=11-14 - 16+13 = 28

-(12-6)+(4-9)=(-12 + 6) + (-5) = (-11)
2009-09-13T11:25:58+02:00
(+12) - (-16) - (+6) + (+20) = 12 + 16 - 6 + 20 = 42
-20 - (-5) + (-17)-(-3) = -20 + 5 - 17 + 3 = -29
-(-11+14)-(16-13) = 11 - 14 -16 + 13 = - 6
-(12-6) + (4-9) = -12 + 6 + 4 - 9 = - 11

Mam nadzieję, że dobrze zrobiłam :)
2009-09-13T11:32:52+02:00
12-(-16)-(+6)+(+20) = 12+16-6+20=42

-20-(-5)+(-17)-(-3) = -20+5-17+3 = -29

-(-11+14)-(16-13) = 11-14-16+13 = -6

-(12-6) + (4-9) = -12 + 6 + 4 - 9 = - 11